2012
DOI: 10.1001/archfacial.2011.1142
|View full text |Cite
|
Sign up to set email alerts
|

Split-Face Double-blind Study Comparing the Onset of Action of OnabotulinumtoxinA and AbobotulinumtoxinA

Abstract: In conclusion, both abobotulinumtoxinA and onabotulinumtoxinA achieved statistically significant onset of action at day 2. This improvement was seen in all end points, with abobotulinumtoxinA demonstrating a trend toward greater improvement than onabotulinumtoxinA at day 2 and a statistically significant greater improvement at days 4 and 6 when looking at maximal contraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 14 publications
3
16
0
2
Order By: Relevance
“…6,16,19,37,43,44 Similar patterns exist for time to maximum effect and are also repeated for different target muscles. 15,16,19 …”
Section: Drug-related Factors Potentially Affecting Onset Of Activitymentioning
confidence: 66%
See 1 more Smart Citation
“…6,16,19,37,43,44 Similar patterns exist for time to maximum effect and are also repeated for different target muscles. 15,16,19 …”
Section: Drug-related Factors Potentially Affecting Onset Of Activitymentioning
confidence: 66%
“…6 A second study found some degree of activity at Day 2 after injection and full onset at Day 6. 19 For the frontalis, utilizing an objective measurement method, a single study found that the median time to onset of activity with a typical dose was 12 to 18 hours, with some patients exhibiting an effect after 6 hours (Table 3). 15,16 …”
Section: The Influence Of Muscle Mass On Abo Efficacymentioning
confidence: 99%
“…Despite these distinctions and anecdotal observations that these products are not interchangeable, clinical studies remain inadequate and have failed to demonstrate consistent substantive differences between neurotoxins. 622 Limited data suggest that incobotulinumtoxinA has a more rapid onset and longer duration, 10 whereas abobotulinumtoxinA has greater spread, 11 and onabotulinumtoxinA has greater strain reduction. 12 Importantly, all neurotoxins elicit similar positive effects on patients’ self-perception of appearance.…”
Section: Neuromodulatorsmentioning
confidence: 99%
“…Botox Cosmetic undergoes a crystallization purifi cation process that yields a 900-kDa complex. The formulation of Botox Cosmetic includes fi ve (5) nanograms of botulinum toxin type A (Hall strain), NaCl, and albumin ( Yu, Nettar, Bapna, Boscardin, & Maas, 2012 ). It is vacuum dried in a 100-unit vial.…”
Section: Botox Cosmetic (Onabotulinumtoxina)mentioning
confidence: 99%
“…Dysport undergoes a chromatographic purifi cation process to yield a 500-to 900-kDa complex ( Yu et al, 2012 ). The formulation of Dysport contains 2.6 ng of botulinum toxin (Hall strain), lactose (to minimize foaming during reconstitution), and albumin; it is vacuum dried in a 300-unit vial for aesthetic use ( Pickett, O'Keeffe, & Panjwani, 2007 ).…”
Section: Dysport (Abobotulinumtoxina)mentioning
confidence: 99%